Short Communication: Analysis of the chemical constituents and micromorphology of Bauhinia scandens using SEM-EDS techniques - LIANAH LIANAH; FATAH IDRIS; KRISANTINI KRISANTINI (Society for Indonesian Biodiversity, 2019)
Abstract. Lianah L, Idris F, Krisantini K. 2019. Short Communication: Analysis of the chemical constituents and micromorphology of Bauhinia scandens using SEM-EDS techniques. Biodiversitas 20: 2055-2060. Some species of Bauhinia had a medicinal efficacy however the specific studies of Bauhinia scandens Willd. are relatively limited. Therefore this study analyzed the material and micromorphological characteristics of leaves, stems and roots of B. scandens using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) to quantitatively assess the elements and explore its potential uses. Samples of fresh plant were taken from five locations in Indonesia, and the results showed similar snake-like stem morphology from two locations, while pilot ladder-like stem morphology was observed from the other three locations. The material analysis revealed the presence of carbon, oxygen, silicon, potassium, indium, tellurium, aluminum and iron in the samples. Interestingly, the stems did not contain indium and aluminum whereas iron were only found in the roots. Furthermore, the young leaves did not contain tellurium and silicon. The presence of indium which is potential as a cancer drug in B. scandens suggests promising uses of the plant for herbal medicines.